Relación de la violencia familiar con el rendimiento académico de los estudiantes del 3er grado de primaria, I.E N°00904 Capironal - Vargas Aguilar, Leidy Jhaneth (2010)
Today's society is undergoing a crisis of vafues, which affects the family as the family, which consists of parents and children. In home environment is often disturbad by problems of both appear as a sudden to become a nightmare for the wildness of the bad characters and behaviors that often drag their aggressors. Of concem to many teachers when they see their students who change their behavior and personality ovemight; notándoles something disturbad them, low selfesteem, anxious, nervous, excited, irritated, which is not good for children and teenagers go through these precarious, as the pair will bring a series of life-long consequences if nothing is done about them. In almost all the homes currently experiencing the syndrome of ''family violence." Many scholars claim that this syndrome occurs for reasons that parents do not have a job, are of low economic status, are alcoholics or drug addicts or otherwise have the drag effect that is what happened to them in their childhood, back to affect their adulthood. Precisely for this syndrome children are psychotogically traumatizad, that is emotionally and sometimes emotional and social, as children find that their parents do not want, due to constant physical and psychological traumas they. receive daily in their homes. For Teaching the problem becomes bigger when the children fall in productivity intellectual achievement. In this research called "List of domestic violence through the academic performance of students in third grade of Primary Education, Educational lnstitution No 00904" Capironal "Rioja district in 2009. 'We as a population sample the number of 29 students who answered a questionnaire of 26 items to gather information on how the treatment they receive from their parents, while the teacher also gave us ínformation on the descriptions obtained in the teaching-leaming process. lt can be seen in a categorical way the oourage of resu1ts on the interpretation and analysis of statistical and mathematical research, the r:esults are alarming in determining that the 71.13% of these boys snd girls suffer ffom this educational institution family violence, also yields information on the academic performance of children in the Third Degree which is 12.48